ONLINE MARKETING STRATEGY IN FACEBOOK MARKETPLACE AS A DIGITAL MARKETING TOOL - Piranda, Dea Resti; Sinaga, Dessy Zulfianti; Putri, Erga Eka (Transpublika Publisher, 2022)
Social media has now become an inseparable part of the daily life of millennials in the digital era. One of the social media that is widely used by millennials is Facebook, which currently has more than 2 billion active users. This places Facebook as one of the foundations of social media that is widely used by social media users. For some people, having a large network of users is the same as money and marketing opportunities, therefore a strategy is needed to use the Facebook platform as a digital marketing tool in an online marketplace that is now increasingly develop. This article aims to find out the use of the Facebook market place as a digital marketing tool and how to use the right marketing strategy on Facebook marketplaces. This descriptive research uses the library method. Based on the findings, Facebook's social media can be said to have complete features because users can communicate with other people, share videos, create a group or association, create a schedule together, and so on. Besides, as a digital marketing tool through the Facebook marketplace, it is now widely used by users for buying and selling activities. Facebook marketplace as a digital marketing tool can be done through several strategies such as advertising, sales promotion, publication of individual sales, and product promotion through the use of visually attractive packaging.